Islamization of English literary studies (Twentieth Century) - Hasan, Md. Mahmudul (2016)
Literature tells us the story of human life. Like any other literary tradition, English literature concerns human beings, their experiences, sorrows and happiness. This is also very much the case with the religion of Islam whose fundamental message is about what is good and what is bad for human beings, as it is about their wellbeing, meaningful existence and responsibilities on earth as God‘s vicegerents (Qur‘an, 21:10 & 2:30). So in terms of the central theme, there is a strong commonality between Islam and literature: both primarily concern human beings. However, one fundamental difference between them is that, the former is infallible revelation from God while the latter smacks of human frailty and arrogance, and other shortcomings and limitations. Accordingly, while we can accept the great bulk of Islamic teachings without any qualms, caution is needed to discriminate clearly what is useful for us in both the worlds from what is harmful when we want to relate the ideas encapsulated in literary works to our life. So it is important for the Muslim practitioners of English literature to analyze ideas and worldviews expressed in it in the light of the flawless, divine blueprint of Islamic teachings. On the basis of this important moral and philosophical framework, in this work, I will assess important twentieth-century English writers and literary pieces from Islamic perspectives, which will provide a direction for the scholars of this literary tradition as to how to approach it Islamically.